2014
DOI: 10.1002/jhet.2205
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Phosphonium Ylides. Part 39: Facile Synthesis of Aziridine, Pyridine, Pyrolotriazole Chromenones and Azaphosphinin Chromenones as Antitumor Agents

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The reaction of 4-azido-2-oxo-2H-chromene-3-carbaldehyde with the active nucleophilic phosphacumulenes yielded the corresponding phosphanylidene-aziridines and chromeno-pyrolo-triazoles. On the other hand, the reaction of the allylic phosphonium ylide, hexaphenylcarbodiphosphorane with the azido compound, was also undertaken. In this case, the phosphanylidene-chromeno-triazinone was obtained. Further assessment of these new compounds against (breast: MCF-7 and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Initial attack by the anion derived from the azido function on the most electron deficient center in the formyl group would afford the dipolar species “ A ,” which undergoes intramolecular rearrangement to afford 9 . It has been reported that o ‐azido‐carbaldehyde compounds can be intracyclized with good yield under the influence of a basic medium …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial attack by the anion derived from the azido function on the most electron deficient center in the formyl group would afford the dipolar species “ A ,” which undergoes intramolecular rearrangement to afford 9 . It has been reported that o ‐azido‐carbaldehyde compounds can be intracyclized with good yield under the influence of a basic medium …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that oazido-carbaldehyde compounds can be intracyclized with good yield under the influence of a basic medium. [16,26] The reaction of compound 1 with the primary amines 4d and 4e was also investigated. Compound 1 reacted with one molar equivalent of 4d or 4e in ethanol at under reflux yielding a mixture of the known Schiff bases 14a or 14b [27] and their α-amino pyrazoles 15a or 15b in each case (Scheme 4).…”
Section: S C H E M E 2 Reactions Of Azidopyrazole (1) Withmentioning
confidence: 99%
“…7). 265 Han, Sheng and Yan described the synthesis of triphenylphosphanylidene spiro[cyclopentane-1,3 0 -indolines] and spiro[cyclopent [2]ene-1,3 0 -indolines] via three-component reactions of triphenylphosphine, isatylidene malononitrile(ethyl cyanoacetate) and but-2-ynedioate or hex-2en-4-ynedioate, respectively (Fig. 7).…”
Section: Preparation Structural Properties and Mechanistic Investigamentioning
confidence: 99%
“…The attention in coumarin derivative chemistry and the biological activities of these compounds has increased through the previous five decades. In follow up to our lab research plan that pointed to the utility of phosphorus reagents in pharmaceuticals synthesis [18][19][20][21][22][23][24][25][26][27][28][29], we expand the previous work on phosphor reagents and coumarins [30,31] to produce unprecedented coumarin derivatives of prospective biological activities, particularly as antioxidants. The methodology depends on the reaction of azidochromene carbaldehyde 1 and 4-azidocoumarin (16) with trialkyl phosphites 2a-c, dialkyl phosphites 7a-c, and hexaalkylphosphorus triamides 11a,b.…”
Section: Introductionmentioning
confidence: 99%